Pair replacement on the spawning success of broodstock Seahorse (Hippocampus barbouri) - . Syafiuddin; M. Zairin Junior; Dedi Jusadi; Odang Carman; Ridwan Affandi (Jurnal Akuakultur Indonesia)
Seahorse, (Hippocampus barbouri) is one of marine living resources having high commercial values and has commonly been traded especially as live ornamental aquarium fish, raw material of traditional medicine and as souvenirs. This expriment was conducted to determine the succces of spawning rate by replacing the broodstock pair of seahorse. This study was done experimentally with treatment of replacement of broodstock pair after spawning under control condition. The experiment was designed to apply completely randomize design by using the following treatments: Treatment A, without replacement neither male nor female. Treatment B, spawned female broodstock  was being mated with her unpaired male broodstock.  Treatment C, a male broodstock that still brood was being mated with his unpaired female broodstock.  Treatment D, a spawned male broodstock that has released larva was being mated with his unpaired female broodstock.  Results showed that under control condition the replacement of broodstock pairs of seahorse had significantly influenced the spawning interval, number of eggs released and number of juveniles produced (P0,05).  It can be concluded that seahorse is not monogamous, either male or female after being spawned may accept other pair for the next spawning.